Urbanisasi dan Perkembangan Pariwisata di Kota Bogor - Agustina Multi Purnomo (Society, 2021)
This study examines the impact of urbanization on tourism development in Bogor City as part of the Jakarta Metropolitan Area (JMA). Previous studies examined the impact of urbanization based on an analysis of urbanization indicators. Inter-city relations in JMA lead to capital and population flows in the form of inter-city migration, development of residential and industrial areas. This study examines the impact of urbanization on tourism development in cities around Jakarta. The argument put forward, urbanization can build a form of city tourism. The study was conducted in Bogor City, a part of JMA, which has experienced urbanization since the royal era and has a variety of tourism services. In contrast to previous research, this study examines urbanization indicator data and the relationship between urbanization history and urbanization indicator data with the development of tourism facilities. The study found that urbanization encourages the development of hotel and restaurant tourism facilities in Bogor City. This is not related to the historical urbanization of the city, other tourism developments, and the relative position of Bogor City among JMA cities. Urbanization encourages the development of tourism facilities through inter-city tourist activity. The research proposes to study the development of tourism facilities as a new perspective on urbanization studies at JMA.